An investigation into the effects of ant control on scale insect populations (Homoptera, Coccoidea) of citrus trees in the Eastern Cape Province, South Africa - Brettell, J H (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1962)
In order that the citrus industry in South Africa may be commercially developed to the greatest possible extent it is of importance that certain basic ecological problems should be investigated. Until the complex relationships between the host plant, the insect pests and their parasites and predators are known, the results of applications of either chemical or biological control must be largely a matter of chance. A certain amount of rather generalised work in this connection has already been done in South Africa, principally by Carnegie (1955), Smithers (1953) and Whitehead (1948) in the Eastern Cape Province and by Steyn (1954) in the Transvaal. The first three of these workers were content to determine which species of insects occurred in citrus orchards and made some attempts to study the biology of certain predators. Steyn went a little further when he correlated ant activity with scale insect infestations. Without doubt the most economically important insect pests of citrus are the scale insects (Homoptera: Coccoidea). Introduction, p. 1.
Keywords: Scale insects -- South Africa; Insect pests -- Biological control